Construção coletiva de uma matriz de indicadores de educação ambiental escolar - Vieira, Solange Reiguel (2016)
To address these emerging contemporary environmental problems, it is essential to the development of environmental education in the training of subjects for citizenship and the enhancement of reflex actions, critical and participatory. In this context, one of the main areas for this to occur is the school, which is challenged to educate for social and environmental sustainability and to be on a sustainable educator space. However, questions arise where to start and the ways to go, so the need to develop evaluation tools. This research aimed to analyze the participatory process of building an array of environmental education indicators to assess the environmental dimension of schools. The empirical field research was nine public schools located in the city of Curitiba-PR. The research subjects were eighty-four participants, faculty, staff, students (over 14 years), educational staff and policy. The chosen methodology was qualitative approach, considering the characteristics of the object and objectives. For data collection was used to document and literature, as well as techniques of participatory methodologies. The research was outlined in two phases, the first for the collective construction of matrix indicators developed in a collaborative school and the second phase to implementation and validation of the constructed matrix, held in eight schools. The analysis of the process supported the improvement of the matrix, which has three dimensions of environmental education: Management, Curriculum and Physical Space, covering ten indicators and descriptors fifty issues. The work with groups of representatives of the school community allowed reflections on the social and environmental conditions of each school, generating knowledge of collective labor and environmental issues from the challenge of establishing evaluation indicators. The results indicated a potential tool to check the current status in relation to the ideas of sustainable school, as well as the possibility of promoting a collective reflection aimed at action-reflection-action. The matrix can be used as a tool for evaluation, management and contribute to the implementation of educational policies and the generation of knowledge in the fields of environmental education and environmental sciences.